Pengaruh Motivasi dan Minat Belajar Terhadap Hasil Belajar Siswa Kelas Xi di SMK Negeri 1 Percut Sei Tuan - Ridho, Ainur; Panjaitan, Dahlya; Simanungkalit, Junika; Manik, Pero Saputra; Sitinjak, Prischilla; Umar, Andi Taufiq (Yayasan Daarul Huda Kruengmane, 2024)
This type of research is Quantitative Associative which aims to determine the effect of motivation variables and interest in learning on improving student achievement / learning outcomes both partially and simultaneously. The population of this study were all class XI students of SMK Negeri 1 Percut Sei Tuan with a sample size of 30 people taken by purposive sampling, namely sampling techniques carried out on the basis of certain considerations of the researcher. The results of this study indicate that learning motivation partially and significantly affects student learning outcomes with a t value = 3.527> t table = 1.662, with a significance value of 0.02 <0.05. Meanwhile, the learning interest variable partially and significantly affects learning outcomes with a t value of 4.479 > t table = 1.662, with a significance value of 0.00 < 0.05. Simultaneously, motivation and interest in learning affect the learning outcomes of class XI students of SMK Negeri 1 Percut Sei Tuan with a value of Fhitung = 6.406> Ftabel = 3.35 The percentage of influence is 39%. These results also explain that the higher the motivation and interest in learning students, the greater the learning outcomes and vice versa. Students with high motivation and interest in learning tend to be more active in learning and vice versa. This research is very important especially in the field of education because it greatly affects the success of a school where high motivation and interest can improve students' abilities so that it has an impact on achieving good and quality learning outcomes, the title we discuss is very interesting to be discussed by further researchers in depth, especially in learning interests that have not been directed to the majors that are really wanted to increase the achievement of student learning outcomes that are superior and can compete with existing majors in vocational schools.